Проблема поглощения человека социальными сетями - Набока, В.; Мороз, К. (ХНУРЭ, 2012)
The problem of social networks in our society is one of the most important problems nowadays. They became the part of our life and our problem too. Information society must understand this. Our young generation use information and internet resource not for raising the knowledge. We must to save them from this social destroying. It is our target.